Esophageal motility classification can be established at the time of endoscopy: a study evaluating real-time functional luminal imaging probe panometry - Carlson, Dustin A. (Gastrointest Endosc, 2019)
BACKGROUND AND AIMS: A novel device that provides real-time depiction of functional luminal image probe (FLIP) panometry, ie, esophagogastric junction (EGJ) distensibility and distension-induced contractility was evaluated. We aimed to compare real-time FLIP panometry interpretation at the time of sedated endoscopy to high-resolution manometry (HRM) in evaluating esophageal motility. METHODS: 40 consecutive patients (ages 24 – 81; 60% female) referred for endoscopy with a plan for future HRM from two centers were prospectively evaluated with real-time FLIP panometry during sedated upper endoscopy. The EGJ-distensibility index (DI) and contractility profile were applied to derive a FLIP panometry classification at the time of endoscopy and again (post-hoc) using a customized program. HRM was classified according to the Chicago Classification. RESULTS: Real-time FLIP panometry motility classification was abnormal in 29 (73%) patients, 19 (66%) of whom had a subsequent major motility disorder on HRM. All 9 patients with an HRM diagnosis of achalasia had abnormal real-time FLIP panometry classifications. 11 (33%) of patients had normal motility on real-time FLIP panometry and 8 (73%) had a subsequent HRM without a major motility disorder. There was excellent agreement (kappa = 0.939) between real-time and post-hoc FLIP panometry interpretation of abnormal motility. CONCLUSIONS: This prospective, multi-centered study demonstrated that real-time FLIP panometry could detect abnormal esophageal motility, including achalasia, at the endoscopic encounter. Additionally, normal motility on FLIP panometry was predictive of a benign HRM. Thus, real-time FLIP panometry incorporated with endoscopy appears to provide a suitable and well tolerated point-of-care esophageal motility assessment.